PENGARUH CITRA MEREK DAN PROMOSI PENJUALAN MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PADA LAUNDRY 5ASEC CABANG MAKASSAR - Andi Widiawati; Muhammad Iwan Syafii (Jurnal Bisnis dan Kewirausahaan, 2017)
The purpose examine is to review determine how far of influence of brand image and sales promotion through social media instagram buying decision against laundry on 5asec Makassar branch. Methods used research is multiple regression analysis, t-test, f-test. Based on the findings of regression analysis so findings that brand image has positive effect buying decision against at laundry 5asec Makassar branch, so the first hypothesis with proven. Based on the findings of the regression processed findings that the sales promotion trhougtsocial media instagramhas a positive impact buying decision against at laundry 5asec Makassar branch, so the second hypothesis with the proposed proven. From the results of hypothesis testing that has done that both variables equally influential joint operations against buying decision at laundry 5aSec Makassar branch, so third hypothesis with proven.